A reflection on narrative based historical memory work in peacebuilding processes. Issue 3 (November 2017) - Edlmann, Theresa
Abstract : N/A: Peacebuilding processes operate within a nexus of historical events, contemporary dynamics and future possibilities. This paper explores the possibilities presented by narrative based historical memory work in enabling an understanding of conflicting stories and perspectives needed to build an understanding of contemporary dynamics of a society or context. The narrative repair created by hearing contrasting stories has the potential to facilitate shifts from previously divisive and exclusionary modes of remembering to more collective ways of moving forward, with lower levels of enmity and violence. The personal insights, as well as the social and relational networks that can emerge out of this work, have the potential to support and undergird the more systemic dimensions of a peace process aimed at addressing legacies of violent conflict.